Memajukan Bisnis Lokal: Pendampingan Pemasaran Online untuk Mendorong Kemandirian UMKM Krupuk Rambak Kulit Sapi Dua Putra Kediri - Risma Siti Nurhayati; Rosa, Selvia Dia; Rohmah, Septia Lutfiatul; Fadila, Septia Nur; Arlency, Shalina Zuan; Mauludin, M. Soleh (Fakultas Ekonomi dan Bisnis Islam, IAIN Kediri, 2024)
This assistance aims to improve the understanding and skills of Dua Putra Kediri MSMEs in online marketing, with a focus on the use of social media to increase sales and product image. The method used is intensive mentoring through observation, interviews, and the presentation of material. The results show satisfaction from the implementation of online marketing, where MSME Dua Putra Kediri succeeded in increasing sales and creating better product branding. MSME owners also expressed their approval for the use of online marketing as a strategy that suits their needs and business development.